Soluções ao conflito negativo de jurisdição internacional: eleição de foro x forum non conveniens - Almeida, Tatiana Tosatti (2019)
The Civil Procedure Code of 2015 brought an innovation in its article 25 when determining the declination of Brazilian jurisdiction when the defendant proves the clause of election of foreign jurisdiction in an international contract, provided that such evidence is made in pleading. This prediction filled the gap that existed in the Civil Procedure Code of 1973, which was not as clear as the declination of Brazilian jurisdiction when there was a foreign court clause, which led most jurisprudence and doctrine to keep the lawsuits considering that, due to competition from the Brazilian courts, the lawsuit could be processed in Brazil. In view of the new provision of art. 25 of the CPC of 2015, it was clear that the Brazilian justice system is not competent to judge actions when there is a foreign court elected under an international contract, if it is alleged by the defendant; analyzing this situation and noting that in commom law countries, notably the US, allow their courts to decline from their jurisdiction because they consider that there is a more convenient forum for prosecution (principle of forum non conveniens), we have seen a possible negative conflict of jurisdiction. The present paper aims to study the hypotheses of negative conflict of international jurisdiction resulting from a foreign forum and forum non conveniens clause that would occur when a plaintiff files a lawsuit in Brazil to discuss conflict arising from an international contract and the defendant proves the existence of a clause electing a US forum, declaring the Brazilian judge as incompetent to prosecute and adjudicate the case; then the plaintiff files a lawsuit in the US and the local court applies the principle of forum non conveniens, as it considers that there was a more convenient forum (in this case, Brazil). Faced with this situation, the plaintiff would remain without resolution of the conflict, which would generate patrimonial damages and legal uncertainty. The purpose of this study is to make considerations about the abovementioned institutes, bringing solutions of international law, but especially, a solution of domestic law, a doctrinal construction on how to deal with this situation from the point of view of Brazilian law, so that the Brazilian courts can hear about the lawsuit and ensure that the plaintiff is granted a fair hearing